Disseminated tuberculosis in elderly-latent activation mimics metastasis: a case study - Chokkalingam, Sitsabesan; Menon, Gopinath; Kumar, Pradeep; Venkatesan, Harish Arvind (International Journal of Research in Orthopaedics, 2023)
Tuberculosis (TB) is an infectious disease caused by mycobacterium species, that affects the lungs and involvement of the musculoskeletal system is not uncommon. Two or more systemic non-contiguous spread is termed as disseminated TB, and its additional involvement of lungs constitute the diagnosis of miliary TB (MTB). Immuno-suppressive conditions including malnutrition and immune-senescence in elderly can predispose to reactivation of latent TB and wide spread dissemination of the bacilli. Screening for dormant TB infection remains an impractical task and its diagnostic confirmation remains a challenge. With raising elderly population, there is a need for a high index of suspicion in the diagnosis of disseminated TB and its management, as delayed approach has increased mortality. Atypical presentation of disseminated TB with concomitant vertebral collapse and extensive lymphadenopathy needs exclusion of metastatic disease although the old nemesis of TB remains a differential diagnosis. We present one such case in a 71 years old lady to highlight the atypical presentation of disseminated TB. The disease presentation had spino-dermal pattern with lympho-reticular involvement including asymptomatic lesions bilaterally in the adrenal glands lesions.